Two Reliable Methodical Approaches for Non-Invasive RHD Genotyping of a Fetus from Maternal Plasma - Bohmova, Jana; Lubusky, Marek; Holuskova, Iva; Studnickova, Martina; Kratochvilova, Romana; Krejcirikova, Eva; Durdova, Veronika; Kratochvilova, Tereza; Dusek, Ladislav; Prochazka, Martin; Vodicka, Radek (Diagnostics (Basel, Switzerland), 2020)
Noninvasive fetal RHD genotyping is an important tool for predicting RhD incompatibility between a pregnant woman and a fetus. This study aimed to assess a methodological approach other than the commonly used one for noninvasive fetal RHD genotyping on a representative set of RhD-negative pregnant women. The methodology must be accurate, reliable, and broadly available for implementation into routine clinical practice. A total of 337 RhD-negative pregnant women from the Czech Republic region were tested in this study. The fetal RHD genotype was assessed using two methods: real-time PCR and endpoint quantitative fluorescent (QF) PCR. We used exon-7-specific primers from the RHD gene, along with internal controls. Plasma samples were analyzed and measured in four/two parallel reactions to determine the accuracy of the RHD genotyping. The RHD genotype was verified using DNA analysis from a newborn buccal swab. Both methods showed an excellent ability to predict the RHD genotype. Real-time PCR achieved its greatest accuracy of 98.6% (97.1% sensitivity and 100% specificity (95% CI)) if all four PCRs were positive/negative. The QF PCR method also achieved its greatest accuracy of 99.4% (100% sensitivity and 98.6% specificity (95% CI)) if all the measurements were positive/negative. Both real-time PCR and QF PCR were reliable methods for precisely assessing the fetal RHD allele from the plasma of RhD-negative pregnant women.
Keywords: real-time PCR; RHD gene; non-invasive fetal genotyping; hemolytic disease of the fetus and newborn; Rh blood group system; QF PCR; red blood cell alloimmunization; cell-free fetal DNA